Klausula Eksonerasi: Akibat Hukum Perjanjian Baku dalam Perjanjian Pengikatan Jual Beli Perumahan - Junaidi, Junaidi (Universitas Batanghari Jambi, 2025)
The principle of freedom of contract allows standardised contracts to be used. However, businesses usually use standard contracts that include exoneration or exclusion clauses because they are in a different position. This can be detrimental to consumers if these clauses limit their obligations and responsibilities. The practice of using standard agreements often occurs when the situation is unstable. Manufacturers change the standard rules. The agreement usually favours the business actors. Although the Consumer Protection Law is already in force in Indonesia, business agreements still use exoneration clauses. However, the existence of such exoneration clauses is still debated in the field of law, according to academic research from legal experts. This study uses a normative legal research approach. Research in the field of normative law focuses on the collection and analysis of current law, legal foundations and ideas, analysis of specific cases, the structure of the legal system, the degree of parallels, comparisons between laws, and the historical development of law. The purpose of this research is to study and provide legal results of the application of exoneration clauses in the binding agreement for the sale and purchase of houses and to resolve default disputes that arise because of housing sale and purchase agreements containing exoneration clauses. The presence of this standard model agreement is still a legal issue, especially in civil law in the field of agreements. Conversely, this new draft agreement may violate consumer rights and even violate the legal rules governing consumer protection. The result is that this research is considered interesting and important to conduct.